Active Vibration Suppression of a Thin Circular Pipe - Pater, Marcin; Leniowska, Lucyna; Grochowina, Marcin (Archives of Acoustics, 2026)
The article presents an active vibration damping system for a thin-walled cylindrical tube, which is a simplified model of a lightweight robot (LWR) arm. The proposed solution integrates control algorithms, piezoelectric materials and a hardware and software environment enabling real-time control. Macro fiber composite (MFC) elements were used for active vibration reduction, acting simultaneously as sensors and actuators. The object on which the research was conducted was a tube with an external diameter of 40 mm, this element was rigidly mounted at a distance of 1 meter from the free end, simulating cantilever conditions. The stimulation of the object to vibration was carried out using the MFC actuator, while the system response was recorded in the xPC Target environment. Based on the measurement data, the mathematical model of the object was identified in the discrete domain using the ARX method. The obtained model was used to design a controller based on the pole location method, which was implemented on a real test stand. The experimental results showed the effectiveness of the designed control system in reducing the amplitude of natural vibrations of the structure. The use of MFC elements as sensor elements and actuators enabled effective vibration damping in real time, confirming the usefulness of the proposed solution in the context of improving the precision of robotic systems.